(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article presents theoretical approaches to the creation of a pedagogical concept for the implementation of a concept based on certain rules when using modern methods of teaching students in higher education institutions.